2021
DOI: 10.1080/09602011.2021.1893192
|View full text |Cite
|
Sign up to set email alerts
|

Navigation ability in patients with acquired brain injury: A population-wide online study

Abstract: The ability to travel independently is a vital part of an autonomous life. It is important to investigate to what degree people with acquired brain injuries (ABI) suffer from navigation impairments. The aim of this study was to investigate the prevalence and characteristics of objective and subjective navigation impairments in the population of ABI patients. A large-scale online navigation study was conducted with 435 ABI patients and 7474 healthy controls. Participants studied a route through a virtual enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 83 publications
(89 reference statements)
2
1
1
Order By: Relevance
“…Beyond this initial encoding difficulty, it is possible TBI cases may have difficulty with a range of 'on-the-fly' processing required to actively navigate, such as mentally tracking travel compared to a plan, spotting the correct goal locations, avoiding recently encountered dead-ends etc. Our findings also agree with the results of van der Kuil and colleagues who found that individuals with ABI show impairments in landmark recognition and allocentric location knowledge and route-based path knowledge [26]. Taken together, there seems to be a consistent pattern of deficits in wayfinding / route finding in TBI patients for both active "game play" navigation (in this current study) and passive "video watching" navigation [26].…”
Section: Plos Onesupporting
confidence: 92%
See 3 more Smart Citations
“…Beyond this initial encoding difficulty, it is possible TBI cases may have difficulty with a range of 'on-the-fly' processing required to actively navigate, such as mentally tracking travel compared to a plan, spotting the correct goal locations, avoiding recently encountered dead-ends etc. Our findings also agree with the results of van der Kuil and colleagues who found that individuals with ABI show impairments in landmark recognition and allocentric location knowledge and route-based path knowledge [26]. Taken together, there seems to be a consistent pattern of deficits in wayfinding / route finding in TBI patients for both active "game play" navigation (in this current study) and passive "video watching" navigation [26].…”
Section: Plos Onesupporting
confidence: 92%
“…Our findings also agree with the results of van der Kuil and colleagues who found that individuals with ABI show impairments in landmark recognition and allocentric location knowledge and route-based path knowledge [26]. Taken together, there seems to be a consistent pattern of deficits in wayfinding / route finding in TBI patients for both active "game play" navigation (in this current study) and passive "video watching" navigation [26].…”
Section: Plos Onesupporting
confidence: 92%
See 2 more Smart Citations